Pengaruh Latihan Sirkuit terhadap Peningkatan Kebugaran Jasmani dan Ketepatan Membidik Panahan pada Anak Usia Dini - Susanto, Susanto (Taallum: Jurnal Pendidikan Islam, 2015)
The current research is conduced to investigate the effect of circuit training on the level of physical fitness and accuracy of shooting of children at 10-12 years old. The research is quasi experimental using two-group pre-test post- test design. The population of the current research is 20 students of SDN Puro Pakualaman Yogyakarta. The data are collected by implementing TKJI test for children and shooting test to measure the accuracy of shooting. The data are taken prior to and after the circuit training with the intensity of 70% - 80%, the frequency of training is three times a week. The trainings are done during 12 -14 times with the duration ofÂ  25-30 minutes. The data are analyzed by using t-test. The findings reveal that (1) there is no significant different of the studentsâ physical fitness, (2) there is significant different of the studentsâ accuracy of shooting, (3) there is an increase of physical fitness and accuracy of shooting of the students who do circuit training. In conclusion, circuit training is effective in improving the accuracy in shooting for children at the age of 10-12 years old.